2014
DOI: 10.1371/journal.pone.0110000
|View full text |Cite
|
Sign up to set email alerts
|

The Acetyl Bromide Method Is Faster, Simpler and Presents Best Recovery of Lignin in Different Herbaceous Tissues than Klason and Thioglycolic Acid Methods

Abstract: We compared the amount of lignin as determined by the three most traditional methods for lignin measurement in three tissues (sugarcane bagasse, soybean roots and soybean seed coat) contrasting for lignin amount and composition. Although all methods presented high reproducibility, major inconsistencies among them were found. The amount of lignin determined by thioglycolic acid method was severely lower than that provided by the other methods (up to 95%) in all tissues analyzed. Klason method was quite similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
148
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(162 citation statements)
references
References 29 publications
3
148
0
Order By: Relevance
“…Considerably, lower estimates were obtained by the ADL method, which ranged from~7 to 14 %. Such striking differences were anticipated and are consistent with the results of previously published comparisons of these lignin methods [23,26,27,29,32,47]. The most likely explanation for the low lignin concentrations obtained by the ADL method is the loss of lignin during the acid detergent extraction of the method [23,32].…”
Section: Large Differences Observed Between the Various Lignin Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…Considerably, lower estimates were obtained by the ADL method, which ranged from~7 to 14 %. Such striking differences were anticipated and are consistent with the results of previously published comparisons of these lignin methods [23,26,27,29,32,47]. The most likely explanation for the low lignin concentrations obtained by the ADL method is the loss of lignin during the acid detergent extraction of the method [23,32].…”
Section: Large Differences Observed Between the Various Lignin Methodssupporting
confidence: 85%
“…More problematically, while all these methods are widely used, large discrepancies are reported in the different estimates of lignin content between them [23,[26][27][28][29][30][31][32]. In a recent study, Fukushima and Hatfield compared the performance of some lignin methods on a number of different plant samples and reported on average a twofold difference in lignin content between the ABL method and the ADL method [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More problematically, while all these methods are widely used, large discrepancies are reported in the different estimates of lignin content between them (Brinkmann et al, 2002, Fukushima & Hatfield, 2004, Goff et al, 2012, Jung et al, 1999, Lacerda et al, 2006, Moreira-Vilar et al, 2014, Takahashi et al, 2004. In a recent study, Fukushima and Hatfield compared the performance of some lignin methods on a number of different plant samples and reported on average a twofold difference in lignin content between the ABL method and the ADL method (Fukushima & Hatfield, 2004).…”
Section: Lignin Fractions As Predictors Of Biomass Quality | 75mentioning
confidence: 99%
“…Recently, Moreira-Vilar and co-workers, compared a number of different lignin methods and concluded that the ABL method outperformed the other methods, primarily because it gave the highest estimates of lignin content (Moreira-Vilar et al, 2014). However, considering that lignin is usually quantified because of its effect on the efficiency of a certain process, for example paper production, ruminant digestion and saccharification for biofuel production, selecting the most appropriate lignin method may depend on which estimate of lignin content has the highest predictive ability of biomass quality for a certain application.…”
Section: Lignin Fractions As Predictors Of Biomass Quality | 75mentioning
confidence: 99%